ANALYSIS OF LATTICE PARAMETER, ERROR, AND THE BANDGAP ENERGY IN CADMIUM SULFIDE (CdS) SEMICONDUCTOR MATERIAL - Kamelia Fikriah; Talitha Alya Syaharani; Fitri Melinda; Lulu Lutfiah; Nada Huwaidah; Agnes Tiara Vinanda; Indriyati Rahmi Setyani; Meutia Awani; Alfi Afriliani; Irmansyah Irmansyah; Irzaman Irzaman (Spektra: Jurnal Fisika dan Aplikasinya)
Has successfully analyzed the lattice parameter, error, and energy band gap of Cadmium Sulfide (CdS) material. CdS is a semiconductor material. In this study, the CdS used is a material with a cubic crystal structure using database from the International Center for Diffraction Data (ICDD), then the data is calculated using the Cramer-Cohen method. From these data the resulting lattice parameter of a = b = c = 5.823791777 Å with an average error of 0.00034%. The band gap energy calculation of CdS material is 2.477 eV.